The impact of moving from an informal settlement to a formal settlement on life satisfaction: a difference in difference analysis - Ngqotheni, Sinakhokonke (My University, 2018)
The aim of study was to trace the life satisfaction of three different groups over four periods of time. The study investigates the impact of moving from an informal settlement to a formal settlement on life satisfaction. Three groups were studied, namely, the treated group, government housing dwellers and private dwellers. The life satisfaction of the three groups is traced using the following five econometric models; Pooled Ordinary Least Squares (POLS), fixed effects, difference in difference (DID), ordinal logit and propensity score matching (PSM). The study results show that the life satisfaction of the government housing dwellers diminished after moving to government housing and was significant throughout DID, ordinal logit and PSM. The private dwellers demonstrated a negative relationship with life satisfaction for the OLS and fixed effects models, DID, nonlinear logit and PSM reported positive with coefficients. The paper found that the location, scale and size of the government houses played an important role in determining life satisfaction.
A research report submitted in partial fulfilment of the Degree of Master of Commerce in the School of Economic and Business Sciences, University of the Witwatersrand, September 2018
Keywords: Squatter settlements--South Africa; Housing--South Africa